The neutralized money stock : an unbiased measure of Federal Reserve policy actions - Hendershott, Patric H. (Homewood, Ill. : R. D. Irwin, 1968)
The book is an extension and elaboration of a doctoral dissertation on Monetary Policy 1952-62. This study is divided into two parts. Part one is money stock response to open-market operations, and part two is on unbiased measure of Federal Reserve policy actions, the impact of the business cycle.
"An extension and elaboration of ... [the author's] doctoral dissertation, Monetary policy, 1952-62, submitted to Purdue University in March, 1965."
Includes index.
Includes bibliographical references: p. 161-165.
usc 05/07/2017
Loans
Keywords: Federal Reserve banks; Monetary policy; United States